2021
DOI: 10.3389/fvets.2021.734973
|View full text |Cite
|
Sign up to set email alerts
|

Relinquishing Owners Underestimate Their Dog's Behavioral Problems: Deception or Lack of Knowledge?

Abstract: Undesirable behavior is a leading cause of canine relinquishment. Relinquishing owners could provide valuable information about their dog's behavior, although the reliability of their reports has been questioned by the sheltering community. This study aimed to investigate (a) whether relinquishing owners' reports of dog behavior differed based on the behavioral screening method; (b) whether relinquishing owners' reports were impacted by the confidentiality of their responses; and (c) whether relinquishing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
0
8
0
2
Order By: Relevance
“…Untreated behaviors have been shown to harm human pet dog relations and, in some cases, quickly. This is likely due to an underestimated commitment of time, money and emotional investment required without guarantees [ 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Untreated behaviors have been shown to harm human pet dog relations and, in some cases, quickly. This is likely due to an underestimated commitment of time, money and emotional investment required without guarantees [ 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Behavioural problems in pet dogs can result in a lifetime in kennels or euthanasia (Patronek et al 1996), and are, along with the need for more attention than owners can provide, a primary reason for relinquishment (Diesel et al 2010). However, behaviour alone is often not the primary determining factor in relinquishment (Patronek et al 2021): also signi cant is owner miseducation in dog behaviour, emphasising the role of owner attitude (Powell et al 2021). Dog behavioural problems are especially salient as a result of the Coronavirus pandemic: in a survey of over 6000 owners, Dogs Trust (2020) found that, during lockdown, 26% of pet dogs had developed at least one new behavioural issue, and an 82% increase in barking and whining.…”
Section: Discussionmentioning
confidence: 99%
“…barking, digging, etc. ), undesired canine behaviours have also been found to be indicative of poor canine welfare (living conditions, inconsistent training, unpredictable social environments), as well as reduced owner attachment (Powell et al, 2021). Further, although several benefits of dog ownership were identified within a 2014 qualitative study exploring the experience of dog ownership for families of children with autism spectrum disorder, 'burdens' were also noted.…”
Section: Introductionmentioning
confidence: 99%
“…Of the available literature exploring reasons for dog relinquishment, behaviour problems are frequently identified (Powdrill-Wells et al, 2021; Powell et al, 2021). In addition to behaviours that reflect instinctual canine behaviour (e.g.…”
Section: Introductionmentioning
confidence: 99%